2001
DOI: 10.1103/physrevb.63.144524
|View full text |Cite
|
Sign up to set email alerts
|

Quantum films adsorbed on graphite: Third and fourth helium layers

Abstract: Using a path-integral Monte Carlo method for simulating superfluid quantum films, we investigate helium layers adsorbed on a substrate consisting of graphite plus two solid helium layers. The solid helium layers are modeled first as inert, with paths frozen at equilibrated positions, and then as active, with second layer atoms included in the Monte Carlo updating. In both cases, we observe the formation of as many as three well defined additional layers above the first two, and determine the layer promotion de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…23 we introduced an approximate local superfluid estimator that was based on the exchange length of Feynman paths. Using this estimator, local decomposition of superfluid and nonsuperfluid densities in the first solvation shell around the molecule yielded rotational constants of SF 6 and OCS molecules inside the helium droplets that are in good agreement with their experimentally measured values. 10,23 However, this exchange-length-based superfluid estimator was only qualitative and did not provide a rigorous decomposition of the global superfluid response.…”
Section: Introductionsupporting
confidence: 73%
“…23 we introduced an approximate local superfluid estimator that was based on the exchange length of Feynman paths. Using this estimator, local decomposition of superfluid and nonsuperfluid densities in the first solvation shell around the molecule yielded rotational constants of SF 6 and OCS molecules inside the helium droplets that are in good agreement with their experimentally measured values. 10,23 However, this exchange-length-based superfluid estimator was only qualitative and did not provide a rigorous decomposition of the global superfluid response.…”
Section: Introductionsupporting
confidence: 73%
“…This experimental fact is also seen in the PIMC simulation of PM. While the simulation 33 indicates that third layer remains liquid at completion, an increased spatial order is observed indicating that the layer at completion is near solidification. While the coverage is continually increased and the fourth layer liquid is built, atoms are observed to go to the third layer.…”
Section: A Helium Filmsmentioning
confidence: 87%
“…The growth of 4 He on graphite can be experimentally studied layer by layer and the coverage per unit surface area for layer promotion can be accurately determined. 28 Pierce and Manousakis ͑PM͒ [29][30][31][32][33] using PIMC, the Carlos-Cole 34 helium-graphite interaction and the Aziz helium-helium potential have found that these promotion coverages can be reproduced within a few percent up to the fifth layer. The first layer phase diagram as a function of coverage and temperature has a ͱ3ϫͱ3 commensurate solid at 1/3 coverage.…”
Section: A Helium Filmsmentioning
confidence: 99%
“…[14], it is shown that the possibility of 3 He atoms moving perpendicularly to the surface leads to a stable liquid phase when the substrate is weakly attractive, as on some alkali metal surfaces. This is probably expected because the system goes from a 2D film to a three-dimensional (3D) configuration where liquid 3 He is the ground-state phase.In this work, we concerned ourselves with the adsorption of 3 He on a clean surface of graphite, trying to reproduce the recent experimental findings of Sato et al[1] Our goal was to bridge the discrepancy between the strictly 2D calculations and the experimental data by improving the theoretical description of the system.Since considering a quasi-two dimensional flat adsorbent is clearly not enough for graphite [14], we included the effects of the substrate corrugation on the behavior of the adsorbate, in line with what has been done previously for 4 He on the same system [15][16][17][18][19][20][21][22]. We found that a corrugated surface is the missing ingredient to reconcile the experimental and theoretical data.…”
mentioning
confidence: 86%
“…Since considering a quasi-two dimensional flat adsorbent is clearly not enough for graphite [14], we included the effects of the substrate corrugation on the behavior of the adsorbate, in line with what has been done previously for 4 He on the same system [15][16][17][18][19][20][21][22]. We found that a corrugated surface is the missing ingredient to reconcile the experimental and theoretical data.…”
mentioning
confidence: 86%